Analyzing monstrous maternal in “Jendela” and “A Mother’s Love” interior mise-en-scene - Dea Aulia Widyaevan (Universitas Padjadjaran, 2023)
Background: The storytelling and narrative approaches surpassed the study of the interior and cinematic by the idea of staging. In film production, the use of interior elements to aid storytelling is called interior mise-en-scene. However, more research still needs to be done on how spatial metaphors in the interior mise-en-scene are explored. The spatial metaphor is central to creating atmosphere and setting based on film narratives. Therefore, this article examines a spatial metaphor in the horror film mise-en-scene, focusing on monstrous maternity. The case studies are the film ‘A Mother’s love’ (Joko Anwar, Indonesia) and ‘Jendela’ (M. Subash Abdullah, Malaysia). Both films portray the woman protagonist as a psychotic character who haunts their own house. Purpose: The article aims to find spatial metaphors to represent the idea of monstrous maternal as a horror motif. Methods: Through qualitative and literature review, the element of the interior mise-en-scene and abjection theory has been analyzed to find meaning in spatial language. Results: As a result, the spatial metaphor in the film portrays the idea of topo analysis- the topography of the intimate being in the house. Many spaces are composed in dream scene situation, and the use of liminal space become central to supernatural narratives. A distorted play camera frames the space, engaging the audience to enter the character’s mind. Implications: This research contributes to how spatial metaphor in film can aid storytelling in interior design. The interior mise-en-scene helps the designer translate the narrative’s text into a spatial dimension through the staging technique.